IMPLEMENTASI KURIKULUM TERSEMBUNYI DALAM PEMBELAJARAN DI TAMAN KANAK-KANAK - Sri Widaningsih (Jurnal El-Audi, 2022)
The implementation of the hidden curriculum in the teaching and learning process will definitely appear, especially in the learning process in kindergarten, whether we realize it or not, this is because the learning process in kindergarten is indeed very dynamic, adjusted to the level of the child's mood. The purpose of this research is to find out what and how this hidden curriculum is implemented. The research approach used is descriptive qualitative, with the main subjects being kindergarten, PAUD and RA children in the city of Bandung. The result of the hidden curriculum implementation process is the achievement of children's developmental tasks optimally, but overall all competency achievements are highly dependent on the condition of the child as a whole. In conclusion, the implementation of the hidden curriculum has a positive impact on improving student learning outcomes.